Instagram as a Digital Learning Medium: An Analysis of @timenzah's Content Quality for Arabic Language Learning at UMM - Arieanti, Charysma Dewita; Abdul Haris; M. Ainur Roziqi (Scidac Plus, 2026)
The rapid development of social media has created new opportunities for language learning, including Arabic; however, systematic analysis of the quality of educational content on digital platforms remains limited. This study aims to evaluate the quality of Arabic learning content on the Instagram account @timenzah as a learning medium for Arabic Language Education students at the University of Muhammadiyah Malang. Using a quantitative survey design, the study involved 24 students who actively accessed the account. Data were collected through a Likert-scale questionnaire based on five dimensions of Jefferson and Tanton’s Digital Learning theory: helpfulness, entertaining, authenticity, relevance, and timeliness. The results of descriptive analysis indicate that the overall content quality falls into the very good category, with an average score of 4.3. Authenticity and helpfulness obtained the highest scores, while entertaining received the lowest, though still positive. Students also perceived the content as effective in improving Arabic vocabulary comprehension. However, learning engagement scored lower than cognitive aspects, suggesting the need for more interactive content elements.